HF radiation pulse source locating in DIN-2K accelerator - Druj, O.S.; Yegorenkov, V.V.; Marchenko, S.V.; Yuferov, V.B. (Вопросы атомной науки и техники, 2022)
Experiments aimed at locating the source generating an HF pulse during the opening of the plasma switch and leading to explosive electron emission at the cathode were performed on DIN-2K pulse accelerator. It is demonstrated that certain lamps glow during the explosive electron emission pulse. This may point to the possible HF pulse generation during the opening of a plasma switch or radial interruption of current. In order to locate the radiation source the FR-2 dielectric insert was introduced into the vacuum diode and Ne lamps were placed over the anode mesh. The thickness of this insert was chosen to be larger than the electron penetration depth. The lack of Ne indicator lamps glow when the anode was shielded by an FR-2 insert was observed as opposed to the case of operation with the vacuum diode as a load. The virtual cathode caused by the explosive emission from the cathode is shown to be the source of HF radiation.